Protective effect of clusterin against interleukin‐1β‐induced apoptosis and inflammation in human knee osteoarthritis chondrocytes - Tachatra Ungsudechachai; Jiraphun Jittikoon; Sittisak Honsawek; Wanvisa Udomsinprasert (Wiley, 2024)
Abstract Chondrocyte apoptosis is recognized as one of the pathological features involved in cartilage degeneration driving the onset and progression of knee osteoarthritis (OA). This study aimed to determine the molecular mechanism underlying the effect of clusterin (CLU), anti‐apoptotic molecule, in human knee OA chondrocytes. Primary knee OA chondrocytes were isolated from the cartilage of knee OA patients and divided into five groups: (1) the cells treated with interleukin (IL)‐1β, (2) CLU alone, (3) a combination of IL‐1β and CLU, (4) LY294002 (PI3K inhibitor) along with IL‐1β and CLU, and (5) the untreated cells. Production of apoptotic, inflammatory, anabolic, and catabolic mediators in knee OA chondrocytes was determined after treatment for 24 h. Our in vitro study uncovered that CLU significantly suppressed the production of inflammatory mediators [nitric oxide (NO), IL6, and tumor necrosis factor (TNF)‐α] and apoptotic molecule (caspase‐3, CASP3). CLU significantly upregulated messenger ribonucleic acid (mRNA) expressions of anabolic factors [SRY‐box transcription factor‐9 (SOX9) and aggrecan (ACAN)], but significantly downregulated mRNA expressions of IL6, nuclear factor kappa‐B (NF‐κB), CASP3, and matrix metalloproteinase‐13 (MMP13). Anti‐apoptotic and anti‐inflammatory effects of CLU were mediated through activating PI3K/Akt signaling pathway. The findings suggest that CLU might have beneficial effects on knee OA chondrocytes by exerting anti‐apoptotic and anti‐inflammatory functions via PI3K/Akt pathway, making CLU a promising target for potential therapeutic interventions in knee OA.